Elevated β-cell stress levels promote severe diabetes development in mice with MODY4. Issue 2 (February 2020) - Trojanowski, Bernadette M; Salem, Heba H; Neubauer, Heike; Simon, Eric; Wagner, Martin; Dorajoo, Rajkumar; Boehm, Bernhard O; Labriola, Leticia; Wirth, Thomas; Baumann, Bernd
Abstract : Maturity-onset diabetes of the young (MODY) is a group of monogenetic forms of diabetes mellitus caused by mutations in genes regulating β-cell development and function. MODY represents a heterogeneous group of non-insulin-dependent diabetes arising in childhood or adult life. Interestingly, clinical heterogeneity in MODY patients like variable disease onset and severity is observed even among individual family members sharing the same mutation, an issue that is not well understood. As high blood glucose levels are a well-known factor promoting β-cell stress and ultimately leading to cell death, we asked whether additional β-cell stress might account for the occurrence of disease heterogeneity in mice carrying a MODY4 mutation. In order to challenge β-cells, we established a MODY4 animal model based on Pdx1 (pancreatic and duodenal homeobox 1) haploinsufficiency, which allows conditional modulation of cell stress by genetic inhibition of the stress-responsive IKK/NF-κB signalling pathway. While Pdx1 +/− mice were found glucose intolerant without progressing to diabetes, additional challenge of β-cell function by IKK/NF-κB inhibition promoted rapid diabetes development showing hyperglycaemia, hypoinsulinemia and loss of β-cell mass. Disease pathogenesis was characterized by deregulation of genes controlling β-cell homeostasis and function. Importantly, restoration of normal IKK/NF-κB signalling reverted the diabetic phenotype including normalization of glycaemia and β-cell mass. Our findings implicate that the avoidance of additional β-cell stress can delay a detrimental disease progression in MODY4 diabetes. Remarkably, an already present diabetic phenotype can be reversed when β-cell stress is normalized.